2015
DOI: 10.1063/1.4921306
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic phase transitions in Ta/CoFeB/MgO multilayers

Abstract: We study thin films and magnetic tunnel junction nanopillars based on Ta/Co20Fe60B20/MgO multilayers by electrical transport and magnetometry measurements. These measurements suggest that an ultrathin magnetic oxide layer forms at the Co20Fe60B20/MgO interface. At approximately 160 K, the oxide undergoes a phase transition from an insulating antiferromagnet at low temperatures to a conductive weak ferromagnet at high temperatures. This interfacial magnetic oxide is expected to have significant impact on the ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Besides, several studies have pointed out the possible influence of strain on second order anisotropy in thin magnetic films 27 28 . For instance in ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, several studies have pointed out the possible influence of strain on second order anisotropy in thin magnetic films 27 28 . For instance in ref.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, several studies have pointed out the possible influence of strain on second order anisotropy in thin magnetic films [26,27]. For instance in Ref [27], the authors observed an anomaly in the tunneling conductance in Ta/CoFeB/MgO based MTJ at low temperatures (T=160K), that they interpreted as a structural-magnetic phase transition of a magnetic oxide formed at the interface between MgO and CoFeB. Magnetic phase transition alters both spintronic and magnetic properties of the MTJ stack.…”
Section: Discussionmentioning
confidence: 99%
“…The alloy can be used as ferromagnetic electrodes in combination with MgO or AlOx barriers to fabricate magnetic tunnel junctions (MTJs) with a very high tunnel magnetoresistive (TMR) ratio [7][8][9][10][11]. It has been known that the crystalline CoFeB film in MTJs has enhanced spin tunneling efficiency and hence can exhibit a higher TMR ratio than the corresponding amorphous one [12].…”
Section: Introductionmentioning
confidence: 99%
“…Noting that equation (6) is based on the assumption that ∂M ∂T is constant in order for Γ to be 2, we should expect the fit of ∂Heff ∂T against H eff (T = 0 K) to pass through the origin for samples with the same free layer composition (and therefore the same M s at T = 0 K). Indeed, by using the gradients and y-intercepts of the H eff plot from figure 4(a) to compare ∂Heff ∂T as a function of H eff (T = 0 K), the experimental results in figure 4(b) are in excellent agreement with equation (6) with the case of proportionality constant, Γ = 2 for CoFeB.…”
Section: Resultsmentioning
confidence: 61%